A. de la Motraye's travels through Europe, Asia, and into part of Africa; with proper cutts and maps : containing a great variety of geographical, topographical, and political observations on those parts of the world; especially on Italy, Turky, Greece, Crim and Noghaian Tartaries, Circassia, Sweden, and Lapland : a curious collection of things particularly rare, both in nature and antiquity; such as remains of antient cities and colonies, inscriptions, idols, medals, minerals, &c. with an historical account of the most considerable events which happen'd during the space of above 25 years; such as a great Revolution in the Turkish Empire, by which the emperor was depos'd; the engaging of the Russian and Turkish armies on the banks of the Pruth; the late King of Sweden's reception and entertainment at Bender; his Transactions with the porte, during his stay of above four years in Turky; his return into his dominions, campaigns in Norway, death, &c. His sister, the Princess Ulrica's accession to the throne, her generous resignation of it to her consort the present king; and, in fine, all the chief transactions of the senate and states of Sweden, &c. - La Mottrage, Aubry de, 1674?-1743. (London)
2 cilt (1. c. [14], 440 sayfa, [2] katlı harita, xxiv yaprak resim (kimi katlı) ; 2. c. 432, 72 sayfa, xxxix, [2] yaprak resim, harita (kimi katlı))